Positive and Negative Politeness Strategies of CC in Family Switch: A Pragmatic Analysis Based on Brown and Levinson’s Theory - Siti Munawarah; Maida Norahmi; Rezqan Noor Farid; Akhmad Fauzan; Ristati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the positive and negative politeness strategies used by the main character, CC, in the movie Family Switch (2023) based on Brown and Levinson's politeness theory. Using a discourse analysis framework, this research identifies and classifies CC's utterances into positive and negative politeness strategies. The primary data are CC's dialogues taken from the movie script and verified by watching the film on Netflix. The findings reveal that CC produces 36 utterances containing positive politeness strategies and 14 utterances containing negative politeness strategies. The most dominant positive politeness strategy is strategy 4: Use in-group identity markers (9 occurrences), followed by strategy 15: give gifts to the hearer (6 occurrences). The most dominant negative politeness strategy is strategy 5: give deference (7 occurrences), followed by strategy 1: be conventionally indirect (3 occurrences). One important finding of this study is that before the body swap, CC mostly uses negative politeness when speaking to her mother. However, after experiencing her mother’s role, she begins to use more positive politeness strategies, such as showing empathy and affection. This finding shows that politeness strategies can change depending on social roles and interpersonal relationships. This study contributes to pragmatics by showing how film discourse can serve as a natural laboratory for understanding real-life politeness adaptation.